SOCIAL RELATIONS IN THE TORAJA COMMUNITY 1945-1947 - Limola, Fajar Sidiq; Makkelo, Ilham Daeng; Amir, Amrullah (Kementerian Pendidikan dan Kebudayaan, 2020)
This research aims to provide an overview of Torajan social relationship, particularly in 1945-1947 when the Dutch took over the government. Toraja is an area with abundant social history, one of them is its social structure. The existence of society groups living in Toraja are related to one another. The relationship between society in their social life is very important, considering that in their daily lives they impose a class system in treating people in Tana Toraja, even it still survives until now. The method used in this research is the historical method ang the initial data collection uses archival and literature studies. The result of this research indicates that the traditional social life of Toraja with a class system, such as Kaunan or slaves and others, is still ongoing, even though the Dutch has abolished the status of slaves in their administrative areas. Besides, this research also shows that the government group is treated as a separate social group by the local people in Toraja.